RESPON TERHADAP RUU P-KS STUDI KASUS: PENOLAKAN PENGGIAT KELUARGA INDONESIA (GiGa INDONESIA) - Rosa, Erina; Noak, Piers Andreas; Putri Wirantari, I Dewa Ayu (Jurnal Nawala Politika, 2021)
Social movements do not only come from workers who are marginalized by the capitalist system, but social movements have turned into new social movements that originate from complaints from community groups regarding changes in government policies whose main problem is inequality of gender relations. By appointing GiGa as an institution rejecting the P-KS Bill. As a theoretical basis, the writer uses Putnam Tong's theory of liberal feminism and McAdam's theory of Political Opportunity Structure. Then the DPR as the holder of power responded by reconsidering the P-KS Bill. This has resulted in various reactions from feminist and conservative movements to those who support and reject the P-KS Bill. The theoretical implication shows that liberal feminism gives a difficult position to the P-KS Bill and the structure of political opportunities affects how the response is given to thwart changes in government policy. Keywords: GiGa, P-KS Bill, Movement, Feminists.